CULTURAL DEVELOPMENTS IN ELECTRONIC LAW ENFORCEMENT IN CRIMINAL ACTS OF THEORY IN INDONESIA - Yusep Mulyana (Lembaga Penelitian Universitas Pasundan, 2021)
The culture of proving electronic evidence in law enforcement of criminal acts of terrorism in Indonesia is Law Number 11 of 2008 concerning Information and Electronic Transactions (